The Role of Biased Earnings Guidance in Creating a Healthy Tension between Managers and Analysts - Mittendorf, Brian; Zhang, Yun (The Accounting Review, 2005)
Analysts and the managers of firms they track have both come under fire in recent years. In particular, managers are accused of using earnings guidance to exert undue influence on analyst forecasts. This paper analyzes optimal incentive contracts that take into account the interaction between analysts and firm managers. In our setting, biased earnings guidance is a natural consequence of contract design. The bias serves to create enough uncertainty so as to motivate the analyst and, thus, may not necessarily be the scourge suggested by conventional wisdom.